Advanced Patellar Tendinopathy Is Associated With Increased Rates of Bone–Patellar Tendon–Bone Autograft Failure at Early Follow-up After Anterior Cruciate Ligament Reconstruction. Issue 11 (15th November 2018) - Lazarides, Alexander L.; Alentorn-Geli, Eduard; Vinson, Emily N.; Hash, Thomas W.; Samuelsson, Kristian; Toth, Alison P.; Moorman, Claude T.; Garrett, William E.; Taylor, Dean C.
Background: Revision anterior cruciate ligament (ACL) reconstruction can be potentially devastating for a patient. As such, it is important to identify prognostic factors that place patients at an increased risk for graft failure. There are no data on the effects of patellar tendinopathy on failure of ACL reconstruction when using a bone–patellar tendon–bone (BPTB) autograft. Purpose/Hypothesis: The purpose of this study was to investigate the association of patellar tendinopathy with the risk of graft failure in primary ACL reconstruction when using a BPTB autograft. The hypothesis was that patellar tendinopathy would result in higher rates of graft failure when using a BPTB autograft for primary ACL reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: All patients undergoing ACL reconstruction at a single institution from 2005 to 2015 were examined. A total of 168 patients undergoing primary ACL reconstruction with a BPTB autograft were identified. Patients' magnetic resonance imaging scans were reviewed for the presence and grade of patellar tendinopathy by 2 musculoskeletal fellowship–trained radiologists; both were blinded to the aim of the study, patient demographics, surgical details, and outcomes. Patients were divided into 2 groups: failure (defined as presence of symptomatic laxity or graft insufficiency) and success of the ACL graft. Statistical analyses were run to examine the association of patellar tendinopathy with failure of ACL reconstruction using a BPTB autograft. Results: At a mean follow-up of 18 months, there were 7 (4.2%) patients with graft failure. Moderate or severe patellar tendinopathy was associated with ACL graft failure ( P = .011). Age, sex, and side of reconstruction were not associated with the risk of graft failure, although the majority of patients who failed were younger than 20 years. The use of patellar tendons with moderate to severe tendinopathy was associated with a relative risk of ruptures of 6.1 (95% CI, 1.37-27.34) as compared with autograft tendons without tendinopathy. Conclusion: Moderate or severe patellar tendinopathy significantly increases the risk of graft failure when using a BPTB autograft for primary ACL reconstruction. Patellar tendinopathy should be considered when determining the optimal graft choice for patients undergoing primary ACL reconstruction with autograft tendons.